Modeling Aggregate Manufactured Exports for Some Asian Newly Industrialized Economies - Muscatelli, Vito Antonio; Stevenson, Andrew A.; Montagna, Catia (The Review of Economics and Statistics, 1995)
Vito Antonio Muscatelli, Andrew A. Stevenson, Catia Montagna, Modeling Aggregate Manufactured Exports for Some Asian Newly Industrialized Economies, The Review of Economics and Statistics, Vol. 77, No. 1 (Feb., 1995), pp. 147-155